Implementation of environmental data explorer for Department of Environment (DOE) - Md. Yusof, Yusnaidi (2003)
Implementation of Environmental Data Explorer (EDE) for Department of Environment (DOE) involves the process of designing a spatial object model, configuring a Spatial Database Engine (SDE) as a gateway that facilitates managing spatial data in a database management system, create and publish metadata into Metadata Service, and use the customised Metadata Explorer to search and browse the contents of Metadata Service from a web browser. The metadata system to be developed is using an e-RAD (enhanced-Rapid Application Development) software development methodology, where it is an adaptation of the Spiral Methodology by which the software development process starts from gaining user requirements, customizing a new or a ready made available modules, and finally launching the prototype or a complete system. This project is using Java Server Pages (JSP) together with ColdFusion and Map Configuration File (AXL) to develop the Environmental Data Explorer (EDE). ESRI's ArcIMS technology was used to build a Web-based environmental data explorer to query, browse, and analyze the environmental metadata. Both ArcIMS, Cold Fusion and Java analysis tools were constructed and customised. The metadata explorer was evaluated with respect to accessibility, navigation, interactive geographic functionality, and spatial analysis functionality. There are four deliverables (some of them being customised) needed to support this project documentation, known as Software Development Plan (SDP), User Requirement and Functional Specification (URFS), and Database Design Description (DBDD; which all of them followed the software documentation standard set by the U.S. Department of Defense (DoD 2167-A) and Military (MILSTD- 498).